Preferred and actual place of death in haematological malignancies: a report from the UK haematological malignancy research network. Issue 1 (11th May 2020) - Sheridan, Rebecca; Roman, Eve; Smith, Alex G; Turner, Andrew; Garry, Anne C; Patmore, Russell; Howard, Martin R; Howell, Debra A
Abstract : Objectives: Hospital death is comparatively common in people with haematological cancers, but little is known about patient preferences. This study investigated actual and preferred place of death, concurrence between these and characteristics of preferred place discussions. Methods: Set within a population-based haematological malignancy patient cohort, adults (≥18 years) diagnosed 2004–2012 who died 2011–2012 were included (n=963). Data were obtained via routine linkages (date, place and cause of death) and abstraction of hospital records (diagnosis, demographics, preferred place discussions). Logistic regression investigated associations between patient and clinical factors and place of death, and factors associated with the likelihood of having a preferred place discussion. Results: Of 892 patients (92.6%) alive 2 weeks after diagnosis, 58.0% subsequently died in hospital (home, 20.0%; care home, 11.9%; hospice, 10.2%). A preferred place discussion was documented for 453 patients (50.8%). Discussions were more likely in women (p=0.003), those referred to specialist palliative care (p < 0.001), and where cause of death was haematological cancer (p < 0.001); and less likely in those living in deprived areas (p=0.005). Patients with a discussion were significantly (p<0.05) less likely to die in hospital. Last recorded preferences were: home (40.6%), hospice (18.1%), hospital (17.7%) and care home (14.1%); two-thirds died in their final preferred place. Multiple discussions occurred for 58.3% of the 453, with preferences varying by proximity to death and participants in the discussion. Conclusion: Challenges remain in ensuring that patients are supported to have meaningful end-of-life discussions, with healthcare services that are able to respond to changing decisions over time.